Pengaruh Perbandingan Tepung Sukun (Artocarpus altilis) dan Tepung Kacang Merah (Phaseolus vulgaris L.) Terhadap Karakteristik Stik - Sombamori Janggat, Alberto; Kencana Putra, I Nengah; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
Breadfruit and red beans are local food ingredients that have many benefits, but the food processing information is still limited and needs development on the using in food products. This research was conducted with the aims to determine the effect of breadfruit flour and red bean flour on the characteristics of stick and to find out the right ratio of breadfruit flour and red bean flour to produce stick with the best characteristics. The Completely Ramdomized Design (CRD) was used in this research with the ratio of breadfruit flour and red bean flour which consisted of 6 levels 100%:0%, 95%:5%, 90%:10%. 85%:15%, 80%:20%, and 75%:25%. The treatment was repeated 3 times to obtain 18 units of experiment. The data were analyzed with Analysis of Variance method and if the treatment had an effect on the variable, the Duncan Multiple Range Test (DMRT) were performed. The results showed that the ratio of breadfruit flour and red bean flour had an effect on water content, ash content, protein content, fat content, crude fiber content, carbohydrate content, texture, color (hedonic test and scoring test), taste (hedonic test), taste of breadfruit (scoring test), taste of red bean (scoring test), and overall acceptance (hedonic test). Ratio of 75% breadfruit flour and 25% red bean flour has the best characteristics with 3.36% water content, 4.71% ash content, 13.77% protein content, 35.00% fat content, 13.63% crude fiber content, 42.62% carbohydrate content, 5.74 N texture, reddish brown and dislike color, does not taste breadfruit, slightly red bean taste, a slightly liked taste, and overall acceptance neither liked nor disliked.